Patients with polycythemia vera have worst impairment of quality of life among patients with newly diagnosed myeloproliferative neoplasms. Issue 10 (October 2013) - Abelsson, Johanna; Andréasson, Björn; Samuelsson, Jan; Hultcrantz, Malin; Ejerblad, Elisabeth; Johansson, Berit; Emanuel, Robyn; Mesa, Ruben; Johansson, Peter
Abstract The quality of life (QoL) at the time of diagnosis of myeloproliferative neoplasm (MPN) has, to date, not been studied. One hundred and seventy-nine patients with MPN: 80 with essential thrombocythemia (ET), 73 with polycythemia vera (PV), 22 with primary myelofibrosis (PMF) and four with MPN undifferentiated, were included in this study. European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC-QLQC30) and the MPN-Symptom Assessment Form (MPN-SAF) were used to evaluate QoL. Fatigue was the most reported symptom in these patients. Patients with PV reported significantly higher mean scores for inactivity, dizziness, cough, itching, depression and lower total QoL compared to patients with ET. Patients with PV had significantly more headache and itching compared to patients with PMF. When the newly diagnosed patients with MPN were compared with a cohort of patients with MPN with mean disease duration of 7.8 years, the differences were most striking for patients with PMF, with significantly more fatigue, abdominal discomfort, concentration problems, insomnia, fever, weight loss and lower overall QoL developed over time.